Visions in the poetry of Yahiya Ibn Hakam AL- Chazali: Visions in the poetry of Yahiya Ibn Hakam AL- Chazali (Journal of the College of Education for Women, 2019)
Conclusion and results1. The research concluded through considering the rhetorical visions,appropriate relationships between utterances with a language derivedfrom the reality of the social, religious, and, cultural life.2. The poet compound between realism and the documentation of thepoetic structure, its depth, and the conjugation of its symbolicmetaphors, and also between its phonetic music and the right artisticnature and the inanimate rules to take in consideration what Dr. AhmadHaikal concluded that the tried to com up with something better thanthat of the previous generation, but he is still following their orbit, andtheir trend method of poem building.3. The realistic images visionary reduces accept the of simile against themetaphoric images which depends on metaphoric and metonymy.These images are considered the bridge between the realistic and themetaphoric and they are the ones our study is interested in.4. The pot did not use much of the images of simile, metaphor, antithesisbut it would be better if he did so.5. Two things appear in AL-Ghazal AL –Janis poetry: spontaneity andintention because he uses a very simple language that goes againstthe rhetorical language that he used in some of his eulogies.6. The poet has a tendency to the analytical side more than his tendencyto concentration. That’s why he master the writing of poetic stories as ifit is a story with a structure including its problem and solution in thefrom of a well build conversation with , the touch of realistic stories thatdepends on conversation in its first stages in Al- Andalus environment.7. His poetry is characterized with the depth of his look to the existingfacts suitability of mood , the easiness of expression , the presences ofspontaneity dearness, frankness , in addition to the wide culture and ofcourse his tendency to the presence of the position and humor8. If we were able to find the poets “collection of poems” the study wouldhave been more rich and precise .The last we can say is our prayers toAllah (be praised) to guide us to the right way to finish this study.